If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 2 + 9a + -19 + 7a + -1 = 136 Reorder the terms: 2 + -19 + -1 + 6a + 9a + 7a = 136 Combine like terms: 2 + -19 = -17 -17 + -1 + 6a + 9a + 7a = 136 Combine like terms: -17 + -1 = -18 -18 + 6a + 9a + 7a = 136 Combine like terms: 6a + 9a = 15a -18 + 15a + 7a = 136 Combine like terms: 15a + 7a = 22a -18 + 22a = 136 Solving -18 + 22a = 136 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 22a = 136 + 18 Combine like terms: -18 + 18 = 0 0 + 22a = 136 + 18 22a = 136 + 18 Combine like terms: 136 + 18 = 154 22a = 154 Divide each side by '22'. a = 7 Simplifying a = 7
| D+28=47 | | 5=6b-7 | | 3x+1z=2 | | 7(a+1)-3a=5+4(29-1) | | -7n-8=104 | | x/-9(-2)=-1 | | 7xy^2-8x^2y+8xy+4xy^2= | | U=-3a-2 | | 9y-6-5y+5=0 | | 8y-3-2y+5= | | 10x-2=128 | | 9x-(2x+9)=8x-24 | | -75=-5x-20 | | (2+6i)+(8-5i)=0 | | -4(6x+2)=-24x-8 | | 8+3n=8n+8 | | 416191*9= | | 5t-6=42-t | | m-6=m | | 2x=(7x-y)+(6-4y) | | 6-2(w+1)=6w-2(6+w) | | 7(s-4)+13= | | .47=log(x) | | 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) |